The Effect of Glycerolisation Time on the Sperm Motility of Local Ram Frozen Semen Diluted in Tris Egg Yolk Extender - Yusuf, T Laswardi; Arifiantini, RI; Mulyadi, Y (ANIMAL PRODUCTION, 2006)
The aims of this experiment was to obtain the effects of  different time of glycerolisation on  the quality of frozen ram semen diluted in Tris Egg Yolk (TEY).  Semen from seven sexually mature local rams were collected using artificial vagina weekly, evaluated macroscopically and microscopically.  Good quality semen then diluted with TEY and 6% glycerol added in three different periods.  The first  step was  diluted in room temperature ( treatment 1), the second glycerolisation was at the end of  equilibration (treatment 2) and the third period was several steps of  glycerolisation during  equilibration (treatment 3). Diluted semen was  packed in straws (Minitub, Germany), equilibrated at 5oC for three  hours,  freezed in liquid nitrogen vapor for 10 minutes and then stored in a container of -196 oC liquid nitrogen.  After 24 hours, the semen was thawed at 37oC for 30 second.  The results of showed that there was no significant differences among treatments (P>0.05).  The percentage of post thawing motility was 42.50% (treatment 1), compared to 38.75% (treatment 2), and 30.00% (treatment 3).  In conclusion, the glycerolization  on frozen ram semen can be done any time of the  equilibration without influencing   the sperm motility. (Animal Production 8(3): 168-173 (2006) Key Words: Glycerolisation, equilibration, ram semen